Main memory database systems: an overview - Garcia-Molina, H.; Salem, K. (IEEE transactions on knowledge and data engineering, 1992)
Main memory database systems (MMDBs) store their data in main physical memory and provide very high-speed access. Conventional database systems are optimized for the particular characteristics of disk storage mechanisms. Memory resident systems, on the other hand, use different optimizations to structure and organize data, as well as to make it reliable. The authors survey the major memory residence optimizations and briefly discuss some of the MMDBs that have been designed or implemented.< >